Portable Urban Agriculture Technology and Soil Nutrient Drive App That Support Farmers Profit - D Nasihien, Ronny; Dhaniarti, Iswachyu; Muhibuddin, Anton; Hasyim, Cholil; Ikhsan Setiawan, M; Ayu Restuti Wulandari, Diah; Zacoeb, Achfas; ., Harimurti; Nyoman Sudapet, I; Napitupulu, Darmawan; Saleh Ahmar, Ansari; Ali, Mahrus; et al. (International Journal of Engineering and Technology, 2018)
A narrow land farmed urban Agriculture. It used for daily fresh vegetables and fruit for the housing community in urban areas. Portable Urban Agriculture Technology as a support facility to increase production of Urban Agriculture, the Greenhouse portable system could be built and transferred to a specific location is convenient, safe, fast, lightweight structural material (PVC 0.55mm Tarpaulin) so that the Urban Agricultural Products closer to residential consumers in urban. The impact was the price was cheaper but quality. The objective was to plan, build and test prototype Water inflated tent activity as a facility to strengthen Greenhouse’s strength, speed, effectiveness and comfort. Application method stages of the Cup or SDN on a former tin mining land, with Portable Urban Agriculture Technology support soil nutrient drive are as follows: first Reconstruction of the land in the form of land arrangement in accordance contours and irrigation channels that exist in the field is very important to support the success of the method SDN; second Management of top soil in the form of top soil enriched with organic material will support environmental compliance in the soil, especially for the growth and development of VAM hyphae and root system; third Soil Amendment to improve the physical and chemical properties of former mining land; fourth Activities vegetation of mined land with SDN method optimizes the achievement of the goals replanting of sustainable of native vegetation for erosion and runoff, repair and restoration of biodiversity, landscape aesthetics that will impact habitat improvement fauna, biodiversity, soil productivity and water quality. Tree plant species such as Acacia mangium, Acacia auriculiformis and Leucaena diversifolia microbes that have been infected with mycorrhizal fungi (VAM) will be very effective and support this effort. Vegetation activities with SDN method includes the following steps: first Seedling plants with VAM; second Preparation of arable land that supports the development of VAM in the soil; third Planting of the first cup with VAM; fourth Incubate 1 month; fifth Planting of the second cup with VAM; sixth 1 month incubation; and seventh The planting of the main crop. Â